Estado actual de los estudios sobre Ausonio: Bibliografía crítica: 1960-1987 - Alvar Ezquerra, Antonio, 1954- (Estudios clásicos, 1991)
A. Alvar offers the whole production on Ausonius between 1960-1987. The items (260) are ordered under seven titles: instrumenta; editions and translations; miscellanea; studies on the historical context and life of Ausonius; linguistic, literary and metrical studies; manuscript tradition and textual criticism; Ausonius' fortune. The paper ends with an index of modern authors referred to the items of the bibliography.